Implikasi Model Pembelajaran Modified Free Inquiry terhadap Kemampuan Tree Thinking Peserta Didik SMA pada Materi Kingdom Animalia - Lamia Putri; Aa Juhanda; Suhendar Suhendar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This research is motivated by the low ability of students' tree thinking, the delivery of animalia material which is still abstract and learning method still teacher centered. So,this research used Modified Free Inquiry learning model which is student-oriented. This study aims to determine the implications of the Modified Free Inquiry learning model on the tree thinking skill of high school students in the Kingdom Animalia lesson. The type of research used in this research is Quasi Experiment with Non-Equivalent Control Group Design research design. The sampling technique used purposive sampling, which are class X MIPA 4 as the experimental class and X MIPA 6 as the control class. The results showed that the tree thinking skill of students in the Kingdom Animalia lesson resulted in an average pretest score of 37.84 and an average posttest score of 81.32 with an N-Gain average score of 0.74 in the high category. Based on the hypothesis test, the significance value of Sig (2-tailed) is 0.000, so H0 is rejected and H1 is accepted. The emergence of the experimental class students' tree thinking skill on each indicator varied but generally had an N-Gain score in the high category. The results of the student response questionnaire regarding the use of the Modified Free Inquiry model show an average score in the very good category (81-100), this is also in line with the teacher's response at the time of the interview. The results of the three instruments in this study indicate that the Modified Free Inquiry learning model has implications for the tree thinking skiil of high school students in the Kingdom Animalia lesson.